The impact of the SARS-CoV-2 pandemic on cardiovascular diseases (Research, Society and Development, 2021)
According to research carried out in China, the place of origin of the pandemic, cardiac injuries have become characteristic of this new virus, reaching about 30% of patients and leading to 40% of deaths. Several changes were observed such as: myocardial injury (20% of cases), arrhythmias (16%), myocarditis (10%), in addition to heart failure (HF) and shock (up to 5% of cases). The objective of this work is to inform and describe the increase in cardiovascular diseases caused by the new virus. And show the importance of more studies on the area. Data were collected using the scientific bases: Latin American and Caribbean Literature in Health Sciences (LILACS), National Library of medicine (PUBMED), PERIODICOS, SCIENCE DIRECT, Virtual Health Library - (BVS), Scientific Eletronic Library Online (SCIELO), Cochrane Library, HighWire Press, Scopus and Elsevier. Approximately 600 articles were found, languages were checked, and if it was really about the correlation of cardiovascular problems and the new virus, then 39 articles were obtained for the discussion. This work concludes that, according to research, there is a great correlation between the virus and cardiovascular diseases and myocardial injuries, due to the increase in troponin, leading patients to major complications. This is also due to the increase in markers leading to cardiovascular injuries.